Comparative Effect of Acetic Acid and Bilimbi (Averrhoa bilimbi L.) Extract on the Extraction and Characteristics of Chicken Skin Gelatin - Mifta Hurahmi; Edi Saputra; Miftahul Khair (Jurnal Pijar MIPA, 2026)
Chicken skin is a potential halal collagen source for gelatin production, especially as an alternative to bovine and porcine gelatin. This study aimed to compare acetic acid and bilimbi fruit extract (Averrhoa bilimbi L.) as acid pretreatment agents for extracting gelatin from chicken skin. The novelty of this study lies in comparing a common food-grade acid with a local natural acid source for sustainable halal gelatin production from poultry by-products. Chicken skin was pretreated with 0.15% NaOH, soaked in acetic acid or bilimbi extract at 2%, 3%, and 4% (m/v) for 24 h, extracted at 65°C for 90 min, and dried at 55°C for 24 h. The gelatin was analyzed for yield, moisture content, ash content, pH, and Fourier Transform Infrared (FTIR) spectra. Data were presented as mean ± standard deviation and analyzed using two-way ANOVA followed by Tukey’s HSD test at p < 0.05. The results showed that gelatin yield ranged from 2.35 ± 0.04% to 10.65 ± 0.07%. Acetic acid produced higher yield than bilimbi extract at the same concentration. The best treatment was 4% acetic acid, which produced the highest yield (10.65 ± 0.07%), low moisture content (9.42 ± 0.08%), low ash content (1.48 ± 0.04%), and pH of 4.48 ± 0.02. FTIR analysis showed amide A, amide B, amide II, and amide III bands, indicating partial hydrolysis of collagen into gelatin. Although bilimbi extract showed lower extraction efficiency, it still has potential as a sustainable local acid source for halal gelatin extraction. These findings support the utilization of chicken skin and local natural resources for sustainable halal gelatin production.